Colored compomer properties - in vitro study (Research, Society and Development, 2022)
Restorative treatment in pediatric dentistry requires a restorative material that has good mechanical properties and is easy to handle and use. Colored compomers for restoration of deciduous teeth are a form of motivation for children in dental treatment, helping them to accept treatment. The objective of this work was to evaluate the surface hardness, compressive and bond strengths of colored compomers. For this, specimens of colored twinky star flow compomers in blue and pink colors (n=15) and bulk fill flow resin were made. To evaluate the bond strength, specimens of colored compomers (twinky star flow in blue) and bulk fill flow resin with were made on bovine enamel (n=16). All were individually conditioned in distilled water for 72 hours in an oven at 37ºC. The values obtained were submitted to the Shapiro-Wilk, Levene tests and one-way analysis of variance. The significance level adopted in all analyzes was 5%. There was no statistically significant difference between the restorative materials in surface hardness, compressive and bond strengths. The pigmentation of the compomers does not interfere in values of surface hardness, compression and bond strength.